KONSEP PENDIDIKAN KARAKTER BANGSA BERBASIS PEMIKIRAN AL-FARABI TENTANG MASYARAKAT IDEAL - Moch. Birrul Akil; Muhammad Hasan Wira Stika; Moh. Rifky Roihansyah; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This article examines the concept of national character education based on Al-Farabi’s thought on the ideal society, known as Al-Madinah al-Fadilah. The study is motivated by the crisis of national identity in the digital era, marked by the weakening of mutual cooperation, increasing individualism, the spread of hoaxes, social polarization, and declining moral sensitivity in society. This research employs a qualitative approach using library research by exploring Al-Farabi’s works, scholarly journal articles, academic books, and relevant educational policy documents. The data were analyzed through content analysis by identifying key themes related to character education, morality, collective awareness, ethical leadership, and social welfare. The findings indicate that Al-Farabi’s concept of the ideal society is highly relevant for reconstructing national character education because it emphasizes cooperation, morality, rationality, spirituality, and the pursuit of shared happiness. This article concludes that character education should not remain a normative program but must become a civilizational project to shape citizens who are ethical, socially responsible, and capable of strengthening national harmony.